Application of cold plasma and ozone technology for decontamination of Escherichia coli in foods- a review. (December 2021) - Niveditha, A.; Pandiselvam, R.; Prasath, V. Arun; Singh, Sushil Kumar; Gul, Khalid; Kothakota, Anjineyulu
Abstract: Unsafe foods and water bodies are the leading cause of disease outbreaks in India and Escherichia coli ( E. coli ) contributes to the majority of food-borne illnesses in human beings. Elimination of food-borne pathogens is of paramount importance in food industries to ensure consumer food safety. Most of the decontamination techniques are thermal in nature and involve the usage of heat that can damage the natural flavor and functionality of foods. Non-thermal oxidation technologies such as cold plasma and ozone can effectively decontaminate E. coli in foods while minimizing quality and nutrient losses . We reviewed recent studies on the application of cold plasma and ozone for the decontamination of food spoilage microbe E. coli. The mechanisms involved and the trending applications are outlined. The effects on microbial activity along with the impact on nutritional, physiochemical and sensorial properties are also discussed. The cold plasma and ozone technology are suitable for the inactivation of E. coli in a wide range of food products and for the surface decontamination. The oxidation principles involved in plasma science and ozone technology could have the potential to replace conventional decontamination techniques in food industries. For maximizing the application, evaluating the treatment parameters with each microorganism and food product can improve the effectiveness and attribute to commercialization of these techniques.